Factors Associated with the Use of HIV Screening in the PMTCT Program by Pregnant Women - Mardohar Tambunan; Sorimuda Sarumpaet; Syarifah (International Archives of Medical Sciences and Public Health, 2020)
Introduction: The Government continues to expand the number ofVCT services (KTHIV) in order to increase HIV testing coverage, asmandated by Ministry of Health Decree No. 74 of 2014 on theimplementation of HIV counseling and testing guidelines. Thepurpose of this study is to ascertain the factors that influence the useof HIV testing in health centers participating in the PMTCT programin the City of Medan in 2015. Method: The study used anobservational design in conjunction with explanatory research and apurposive sampling technique. This research sampled as many as 91pregnant women's. The results of this study will be analyzedmultivariate using the multiple logistic regression test. Result : Thefindings indicate that employment of pregnant women (p = 0.031),knowledge (p = 0.001), attitude (p = 0.001), and family support (p =0.003) are all associated with pregnant women's actions during HIVexaminations. Pregnant women's employment (p = 0.027),knowledge (p = 0.039), attitude (p = 0.004), and support from healthcare providers (p = 0.023) all influence the steps pregnant motherstake to obtain an HIV test. The primary factor preventing pregnantwomen from conducting HIV tests at the Padang Bulan public healthoffice is their negative attitude toward HIV testing (Exp = 7.167).Conlusion: The research findings indicate that Padang Bulan publichealth office prenatal care and HIV testing services should beenhanced. Padang Bulan public health office makes people feel atease and cared for, which is why those who have previously used theprenatal care and HIV testing services will return to perform theexamination. As a responsible program, the Medan City HealthDepartment's Prevention of HIV Transmission from Mother to Childshould establish collaborations with non-governmental organizations(NGOs) that work on HIV / AIDS.